New ATRP initiator for synthesis of cyclic carbonate-terminated poly(methyl methacrylate) - Palaskar, Dnyaneshwar V.; Sane, Prakash S.; Wadgaonkar, Prakash P. (Reactive & Functional Polymers, 2010)
A new ATRP initiator, viz, 2-oxo-1,3-dioxolan-4-yl-(methyl-2-bromo-2-methylpropanoate) (ODMBMP) was synthesized by the reaction of commercially available glycerol carbonate with 2-bromoisobutyrylbromide and was used to carry out ATRP reactions of methyl methacrylate (MMA) in the presence of copper chloride/N,N',N',N''N''-pentamethyldiethylenetriamine to afford low molecular weight (M(n)(GPC) = 1750-7550) cyclic carbonate-terminated poly(methyl methacrylate)s with relatively narrow molecular weight distribution (M(w)/M(n) = 1.16-1.30). Poly(methyl methacrylate)s having higher molecular weight (M(n)(GPC) = 18,250 and 44,130) could also be synthesized using ODMBMP as the ATRP initiator. The kinetic studies of bulk ATRP of MMA showed a linear relationships between both In[M](o)/[M(t)] vs time and molecular weight vs conversion indicating controlled/living polymerization. The presence of cyclic carbonate functionality in poly(methyl methacrylate)s was confirmed by FUR. (1)H NMR, and (13)C NMR spectroscopy. The reactivity of cyclic carbonate group was demonstrated by a model reaction using n-propyl amine and the results showed quantitative conversion to hydroxyl urethane group. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Atom transfer radical polymerization (ATRP); cyclic carbonate; functional polymers; poly(methyl methacrylate)